The Role of the Baldwin Effect in the Evolution of Human Musicality - Podlipniak, Piotr (Frontiers in Neuroscience, 2017)
From the biological perspective human musicality is the term referred to as a set of abilities which enable the recognition and production of music. Since music is a complex phenomenon which consists of features that represent different stages of the evolution of human auditory abilities, the question concerning the evolutionary origin of music must focus mainly on music specific properties and their possible biological function or functions. What usually differentiates music from other forms of human sound expressions is a syntactically organized structure based on pitch classes and rhythmic units measured in reference to musical pulse. This structure is an auditory (not acoustical) phenomenon, meaning that it is a human-specific interpretation of sounds achieved thanks to certain characteristics of the nervous system. There is historical and cross-cultural diversity of this structure which indicates that learning is an important part of the development of human musicality. However, the fact that there is no culture without music, the syntax of which is implicitly learned and easily recognizable, suggests that human musicality may be an adaptive phenomenon. If the use of syntactically organized structure as a communicative phenomenon were adaptive it would be only in circumstances in which this structure is recognizable by more than one individual. Therefore, there is a problem to explain the adaptive value of an ability to recognize a syntactically organized structure that appeared accidentally as the result of mutation or recombination in an environment without a syntactically organized structure. The possible solution could be explained by the Baldwin effect in which a culturally invented trait is transformed into an instinctive trait by the means of natural selection. It is proposed that in the beginning musical structure was invented and learned thanks to neural plasticity. Because structurally organized music appeared adaptive (phenotypic adaptation) e.g. as a tool of social consolidation, our predecessors started to spend a lot of time and energy on music. In such circumstances, accidentally one individual was born with the genetically controlled development of new neural circuitry which allowed him or her to learn music faster and with less energy use.